Strategi Branding Elshinta Radio Dalam Membangun Positioning Sebagai Radio Berita - Muhammad Nevo Bizaro; Velda Ardia; Jamiati KN (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2023)
Elshinta Radio is a radio station that broadcasts full news broadcasts for 24 hours non-stop and without song interludes, and is the only radio station in Indonesia that has a broadcast concept like this. The research entitled "Elshinta Radio Branding Strategy in Building Positioning as a News Radio" has the aim of identifying the Branding Strategy carried out to build Elshinta Radio's Positioning as a news radio as well as the obstacles that exist in Elshinta Radio implementing its Branding Strategy. The theory used in this research is Gelder's theory, where this research uses a qualitative descriptive method which is accompanied by data collection techniques using structured interviews and observations and assisted by documentation as complementary evidence. Then the data that has been obtained is then continued to analyze the data by means of data reduction, data presentation and summary. From all the stages that have been carried out, the results of this research can be analyzed that Elshinta Radio uses a branding strategy in the form of brand positioning, brand identity and brand personality in forming brand positioning. In carrying out this branding, they actually think that there are no obstacles, but they think that it is a challenge that must be resolved and overcome well. However, there is one obstacle that occurs, namely maintaining the consistency of the competencies possessed by each existing human resource. Maintaining consistency is a current obstacle for Elshinta Radio.